Metrificação da memória de trabalho nos elementos do material design: experimento em um protótipo para smartphone - PINHEIRO, Lucas Mendes (2023)
Memory is a broad field of study, with various perspectives on it. Currently, it is understood that the brain utilizes multiple structures to form memory storage. Despite not knowing the true capacity of human memory, it remains an essential part of everyday artifact usage, hence the relevance of this topic in digital interface design. In the current context, where smartphones have become essential tools in human daily life, an increasing number of digital artifacts are being developed based on design principles. Many of these principles and their applications have been cataloged in a system created by Google to assist teams in developing high-quality experiences that resonate with the audience. These elements rely on mental models, which attempt to replicate established patterns to reduce the user's learning curve when using a particular digital artifact. However, the ideal scenario, where faithfully reproducing these patterns can effectively solve the problems faced by those involved in interface design projects, does not seem to be a constant. Considering that existing procedures for evaluating the "cost of memorability" of an easily accessible digital interface are either non-existent or only tangentially aligned with the intentions of professionals, and that certain widely adopted tools in the market already capture and generate efficiency reports (task success), efficacy metrics, screen recordings, and heat maps, aligning this practice with a data-driven approach in design projects, the research objective was raised: to analyze whether the combined use of commonly used market techniques is effective in measuring the cost of memorability in smartphone interfaces, in order to provide recommendations for structuring metrics that assist in evaluating the patterns' level of memorability difficulty. To achieve this, a study was designed that allowed for the validation of metrication for the memorization cost of interface flows through quantitative experiments. The results yielded a database with task success rates, completion times, and the percentage of heat map filling. These investigations demonstrated a potential correlation between task efficiency and interaction objectivity, as indicated by the relationship between the percentage variation between screens and the standard deviation of filling.